Spatial and Temporal Dynamics of Sexual Segregation in Kashmir Markhor Capra falconeri cashmiriensis in Chitral Gol National Park - Khan, Shah Fahad Ali; Nisa, Mehroon; Naz, Shagufta (Indus Journal of Bioscience Research, 2025)
The study explores the spatial patterning and social grouping of Kashmir Markhor (Capra falconeri cashmiriensis) populations in Chitral Gol National Park, Pakistan, through systematic scoring of the Social Segregation and Aggregation Statistic (SSAS) during different seasons and across various habitat types. This research is particularly significant given the vulnerable status of the Kashmir Markhor and the need for informed conservation strategies. Data were collected through point and focal animal sampling every fortnight over a span of two years in diverse park habitats. The study revealed variation in behavior across habitats, with aggregation behavior dominating in the forested areas. This behavioral tendency may reflect the species’ preference for cover and resources in densely vegetated landscapes. The Kruskal-Wallis H-test indicated no significant differences in SSAS values across winter, spring, summer, and autumn, suggesting that the spatial behavior of markhor remains consistent across seasons. These results provide a comprehensive overview of how seasonal and habitat-related factors influence social behavior in this endangered species. Such insights are crucial for wildlife managers and conservationists working to protect and maintain healthy populations of the species in the wild. These findings are valuable for managing vulnerable Markhor populations by enhancing understanding of their social structure and movement patterns in Chitral Gol National Park. The study contributes meaningfully to the ecological literature on ungulate social behavior and offers guidance for future research aimed at long-term conservation planning in protected mountainous ecosystems.